PENERAPAN KRITERIA KEMANTAPAN KAWASAN KESATUAN PENGELOLAAN HUTAN LINDUNG (KPHL) UNIT XIV TOBA SAMOSIR - Intan Yusarga Virnalisi Simarmata; Nurul Qomar; Evi Sribudiani (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
The purpose of this study was to find out the application of area stability criteria of Protected Forest Management Unit (PFMU) of Unit XIV Toba Samosir and to find out the factors that influence the performance of PFMU Unit XIV Toba Samosir in area stabilization. This study was used criteria and indicator from Forest Watch Indonesia version 1.0. Data collection was done through documentation studies, field observations and in depth interviews. Data analysis was done by giving an assessment of each quality element of each indicator. The results showed that the average of assessed criterias was 2,166 which was in sufficient range, which means PFMU Unit XIV Toba Samosir was quite good at carrying out its functions as a forest management unit at the site level. The factors that influence the development performance of PFMU Unit XIV Toba Samosir in area stabilization was forest land tenure conflict with the community around the PFMU Unit XIV Toba Samosir area which caused the absence of boundary arrangements throughout the perimeter of the forest area, human resources that were inadequate in conflicts resolution and the implementation of socialization to the community, and management funds are still limited. Keywords: application, area stability, criteria, KPHL